Automate Classroom and The Culture Adaptation - Setyaningsih, Endang (KnE Social Sciences, 2020)
The 4.0 industrial revolution has stimulated advance technology and automation, which is in turn encouraging the redesign of elementary school teaching programmes. The curriculum update leads to learning automation as consequence of digitalization. Teaching methods are increasingly shifting towards automate dsystem in digital classrooms. The purpose of this research is to show the prototype of an automation classroom, and how to adapt classroom automation into sustainability culture. This paper discusses the major impact of education reformation and the culture adaptation on elementary schools. This paper employed the qualitative research by analyzed the development of augmentation process and the cultural sustainability in the future education. The findings suggest that the latest development of automated classrooms are creating a positive impact on the competitiveness of schools. By updating the curriculum wisely, it is possible to integrate education with technology and benefit the children being taught. Keywords: automate classroom, education revolution, culture adaptation, cultural sustainability